Psychometric properties of the Chinese version of the contesting orientations scale among Chinese undergraduates - Chen, Tianxia; Li, Wanlin; Ren, Yilin; Zhang, Huiqin; Zhu, Fengshu (Frontiers in Psychology, 2025)
ObjectiveTo modify the Contesting Orientations Scale (COS) and test its internal consistency, stability over time, construct validity, and convergent validity in conjunction with the Chinese context.MethodsA preliminary COS test was conducted on 120 college athletes nationwide (116 valid questionnaires were collected). Then, project analysis and exploratory factor analysis were used to determine a formal scale. Finally, 235 college athletes were selected for formal testing (227 valid questionnaires were recovered), and confirmatory factor analysis and internal reliability test were conducted on them; In addition, this study also used the Competitive Psychology Scale for College Students (PPCSCS) as the research object for the convergent validity of standards, and studied the correlation between competitive psychology and competitive orientation. After 1 month, 150 subjects were selected for retesting.ResultsThe Chinese version of COS contains 12 entries, including two dimensions: partnership and war; The confirmatory factor analysis results show that the scale has good structural validity (χ2 = 108.67, df =53, RMSEA = 0.07, NFI = 0.91, CFI = 0.95, GFI=0.93, PGFI = 0.63), The correlation coefficient between the scores of various dimensions of COS and the total score of PPCSCS ranges from 0.61 to 0.81 (P < 0.01). The total internal consistency coefficient of the scale is 0.79, and the retest reliability is 0.78. The internal consistency of the two dimensions of partnership and war are 0.85 and 0.88, respectively. After deleting a certain entry, Cronbach's α was not found. The significant change is that the discrimination between the various items of the scale is good, with a Guttman half reliability coefficient of 0.71 and retest reliability of 0.83 and 0.86, respectively.ConclusionThrough the competition orientation scale tested in the group of college athletes in Jiangsu Province, China, there are good measurement indicators in the selected sample of college athletes, which can predict the competition orientation of college athletes in Jiangsu Province, China and their sports personality. Future research should expand the sampling range, and sample from multiple regions and age groups to test the applicability of the Chinese version of COS, and promote it on a larger scale.